1996
DOI: 10.1007/bf02272132
|View full text |Cite
|
Sign up to set email alerts
|

Practical experience with organic solvent flow field-flow fractionation

Abstract: SummarySeveral types of membrane have been tested for use in organic solvent flow field-flow fractionation in an asymmetric channel. The practical problems most commonly encountered were leakage of air and solvent through the SUpport layer on which the membranes are cast, and Unequal swelling of the membrane and the support layer m the organic solvent, leading to ridging of the membrane in the channel. Three types of membrane Were found suitable for the separation of polystyrene standards with tetrahydrofuran … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In flat-channel asymmetrical flow FFF, in which the membrane is clamped between two plates, swelling of the support of the membrane can lead to deformation or rupturing of the membrane. 7 A module has been developed to contain the hollow-fiber membrane that was inspired by a setup developed by Jo ¨nsson and Carlshaf 11 but that has the advantage that it is built completely of standard liquid chromatography equipment. All connections to the fiber consist of Teflon and stainless steel, which are resistant to all but the most aggressive solvents.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In flat-channel asymmetrical flow FFF, in which the membrane is clamped between two plates, swelling of the support of the membrane can lead to deformation or rupturing of the membrane. 7 A module has been developed to contain the hollow-fiber membrane that was inspired by a setup developed by Jo ¨nsson and Carlshaf 11 but that has the advantage that it is built completely of standard liquid chromatography equipment. All connections to the fiber consist of Teflon and stainless steel, which are resistant to all but the most aggressive solvents.…”
mentioning
confidence: 99%
“…In search of a suitable membrane, researchers have made use of cellulose nitrile, , modified cellulose, and polyaramide materials . Wijnhoven et al have tested several other membrane types and summarized the main practical bottlenecks of organic solvent flow FFF. Although it was found that in principle organic solvents can be used, the long-term stability of the membranes was generally quite poor, and adsorption of solutes to the membranes frequently occurred, having an adverse effect on the separation efficiency.…”
mentioning
confidence: 99%
See 1 more Smart Citation